Enhancing Foreign Students’ Writing Skills through Visual Media: Addressing Vocabulary Acquisition Challenges - Zuindra Zuindra; Mayasari Mayasari; Misla Geubrina; Norlili Juwita Arshad; Nik Intan Baizura binti Ramsa (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2026)
Background:Writing remains one of the most challenging skills for foreign language learners, particularly due to limited vocabulary knowledge and difficulties in organizing ideas into coherent texts. Although visual media have been widely recognized as effective tools in language learning, limited research has specifically examined how structured visual media support vocabulary development as a pathway to improving writing performance in authentic classroom contexts. This study aims to investigate how the classroom use of visual media enhances vocabulary acquisition and writing skills among foreign students. Methodology:This study employed a qualitative descriptive design in an intermediate writing class at a private university in Indonesia, involving ten foreign students. Data were collected through classroom observations, semi-structured interviews, and analysis of students’ written texts. The collected data were analyzed using thematic analysis to identify patterns related to vocabulary use and writing development. Findings:The findings showed that the use of visual media contributed positively to students’ writing development. Students’ average writing scores increased from 58.9 to 76.6, while the average number of vocabulary items used in their writing improved from 9 to 15 words. In addition, students became more confident in generating ideas and were able to organize their writing more coherently. The visual prompts provided contextual support that helped students retrieve vocabulary more easily and apply it more effectively in their writing tasks. Conclusion:The integration of structured visual media provides meaningful contextual scaffolding that helps learners bridge vocabulary knowledge and its practical application in writing, thereby improving writing performance in authentic EFL classroom settings. Originality:This study contributes to the literature by demonstrating that the classroom integration of structured visual media supports vocabulary development as a critical mechanism for improving writing performance, addressing the underexplored link between vocabulary acquisition and actual writing outcomes among foreign students.